The academic hurdle race : a case study - Toren, Nina [Verfasser]; Moore, Dahlia [Verfasser] (My University, 1998)
This study analyzes the career patterns of a cohort of faculty members in a large Israeli university and shows that women constitute a small minority in that university, and that their rank advancements are fewer, slower, and lower than men-s. We examine three possible explaining mechanisms: (a) "Thresholds" -according to which after women cross a certain barrier, differential career development on the basis of gender disappears or is, at least, greatly reduced. (b) "Ceilings" -according to which women-s advancement is curbed before they reach the highest rank. (c) "Hurdles" -according to which women, as compared to men, are confronted by more obtrusive barriers at each step of the academic career. We found that no threshold could be detected after which gender differences are reduced and that the ceiling effect may be a by-product of women-s extended career paths. Rather, the analysis of the case study suggests that women-s career trajectories are characterized by "hurdles", i.e., at each rank they stay longer and their advancement probability is lower than men-s even when their publication rates are taken into account. (author-s abstract, IAB- Doku) ((en)) Untersucht wird der Berufsverlauf einer Kohorte von wissenschaftlichen Fakultätsmitgliedern einer der grössten israelischen Universitäten über einen Zeitraum von 25 Jahren unter dem Blickwinkel von geschlechtsspezifischen Unterschieden und typischen Erklärungsmustern. Es stellt sich dabei heraus, dass Frauen an jeder Station ihrer beruflichen Universitätskarriere spezifische Hürden überwinden müssen. (IAB)
Keywords: S 6.4 Dienstleistungsberufe; S 3 Institutionen; G 1.3.3 Bildungs- & Erwerbsbiografien; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; P 1.3 Frauen; P 3.2.3 Lehrer; I 2.3.4 Asien; Wissenschaftler; Universität; Berufsverlauf; Geschlechtsspezifische Faktoren; Berufsproblem; Frauen in Einzelberufen; Frauenarbeit; Lehrer; Hochschullehrer; Israel; 1960-1985